Substance-Related Problems in Adolescents with ADHD-Diagnoses: The Importance of Self-Reported Conduct Problems. Issue 14 (December 2022) - Heradstveit, Ove; Askeland, Kristin Gärtner; Bøe, Tormod; Lundervold, Astri Johansen; Elgen, Irene Bircow; Skogen, Jens Christoffer; Pedersen, Mads Uffe; Hysing, Mari
Background: Attention-deficit/hyperactivity disorder (ADHD) is a known risk factor for substance-related problems (SRP) during adolescence, but the nature of this relationship and the importance of co-occurring conduct problems are not fully understood. Methods: Data stem from a linked dataset between a large population-based survey conducted in 2012 of Norwegian adolescents aged 16 to 19, and registry-based data from specialized child and adolescent mental health services ( n = 9, 411). Results: Adolescents with "ADHD + high conduct problems" had increased risk of SRP (odds ratios = 2.37–10.14). Adolescents with "ADHD only" had very similar risk of SRP as adolescents from the general population with low symptoms of conduct problems. Relative to boys, girls with "ADHD + high conduct problems" appeared to have somewhat higher risk for SRP. Conclusion: The present study suggests that the risk for SRP among adolescent with ADHD is largely driven by co-existing conduct problems.